337 Expansion of Dendritic Cells Using FLT3 Ligand to Treat Glioblastoma: A Preclinical Study. (August 2016) - Garzon-Muvdi, Tomas; Mangraviti, Antonella; Theodros, Debebe; Kim, Eileen; Yellin, Michael Jay; Marsh, Henry; Lim, Michael
Abstract : INTRODUCTION: FLT3L induces expansion and recruitment of plasmacytoid dendritic cells (pDCs) into the brain. By increasing antigen presentation, FLT3L agonists may enhance an immune response against glioblastoma (GBM). Previous results suggest that the antitumor response generated by FLT3 is secondary to production of interferon gamma. We studied the effect of FLT3L treatment of mice with a syngeneic GBM model. METHODS: Under ACUC approval, 32 mice underwent implantation of 130 000 GL261 cells in the left striatum using a stereotactic frame. The presence of tumor was confirmed by bioluminescence imaging at day 7. Mice were randomly assigned to 4 groups: Control, FLT3 (courtesy of Celldex) treatment, Poly IC treatment, and FLT3+Poly IC treatment. Survival was assessed using log-rank analysis and described using Kaplan-Meier curves. RESULTS: A survival experiment demonstrated that FLT3L treatment of mice resulted in 50% long-term survival of mice and improved survival compared with control groups ( P = .001). Addition of Poly IC (TLR3 agonist), did not add survival benefit. CONCLUSION: The present work suggests that an increase in antigen presentation by enhancing and recruiting dendritic cells into the brain and brain tumor may be beneficial and a potential therapeutic strategy for patients with GBM. The mechanism of this phenomenon is currently under investigation, but includes increased secretion of interferon gamma. Additionally, increased antigen presentation may aid the immune system mount a significant antitumor immune response. Further experiments evaluating the proportion of T cells that have been exposed to antigen are currently underway.